Availability and Utilization of Information and Communication Technology among Instructors in Adult and Non-Formal Education Centers in Kwara State, Nigeria - Ambali Taiwo Toyin; Abdullahi Abdulazeez Kolapo; Sholagberu Abdulsalam Oladimeji; Kayode Sadiq Toyin (The Open University of Sri Lanka, 2021)
This study examined the availability and utilization of information and communication technology (ICT) among instructors in adult and non-formal education centers in Kwara State, Nigeria. Three objectives were raised and translated to research questions to guide the study. A descriptive survey research design was adopted for the study and 271 was considered as the target populations comprising male and female instructors. A sample size of one hundred and sixty (160) respondents was selected across the State. A multi-stage sampling procedure consisting of cluster sampling, purposive sampling and simple random sampling was adopted. Check list and questionnaire were used as an instrument for data collection for the study. The reliability of instruments was achieved using test-retest technique and a co-efficient 0.82 was obtained. The administration of the instruments was carried out by the researchers and five volunteer field research assistants. The data collected was analyzed using frequency count and percentages. One of the findings revealed that the level of utilization of ICT among instructors was low. It is therefore, recommended that there is a need to create awareness among instructors on the level of utilization of ICT to increase the level of consciousness for effective teaching learning process.